Influence of exogenous abscisic acid on physiological responses of Dendrobium candidum under drought stress - Feng-xia Tian; Guang-ling Xu; Cai-xia Wang; Yu-qing Wei; Suo Zhou (Acta Botânica Brasílica)
Abstract: Abscisic acid (ABA) is a naturally occurring plant hormone, and it is also a known stress hormone that acts in plant responses to abiotic stresses, especially drought. Dendrobium candidum production losses due to drought have prominent economic effects. The current study investigates the role of ABA in the drought stress tolerance of D. candidum. The influence of drought stress and foliar spray with ABA at different concentrations (5 mg/l, 10 mg/l, 15 mg/l) on physiological and biochemical parameters was analyzed. The stems and leaves of D. candidum were collected on Day 0, Day 6, and Day 12. The osmotic regulation ability, photosynthetic maintenance ability, and antioxidant ability of D. candidum under drought stress were measured. Additionally, the changes in growth and physiological characteristics of D. candidum under drought stress were studied after applying three concentrations of ABA. Exogenous ABA application effectively ameliorates the adverse effects of drought stress to improve drought resistance. In conclusion, 10 mg/l ABA resulted in leaf water status maintenance, photosynthetic performance, and antioxidative ability under drought stress.